Turbulent Shear Flows in Aerospace and Automotive Engineering: A Review - Sandeep Tyagi (Journal of Advanced Research in Mechanical Engineering and Technology, 2025)
Turbulent shear flows are a critical phenomenon in aerospace and automotive engineering, significantly influencing aerodynamic performance, fuel consumption, thermal management, and structural integrity. These complex, chaotic fluid motions arise due to velocity gradients within a flow field, leading to increased drag, unsteady lift forces, and heat transfer effects that impact the efficiency and stability of vehicles. Understanding the mechanisms governing turbulent shear flows is essential for improving vehicle design, reducing energy losses, and enhancing overall operational performance. This review provides an in-depth exploration of turbulent shear flows, including their fundamental characteristics, governing equations, and the role of boundary layer interactions in high-speed transportation systems. The impact of turbulence on aerospace applications, such as aircraft wing aerodynamics, shock-wave boundary layer interactions in supersonic and hypersonic vehicles, and wake turbulence in flight formation, is examined in detail. Similarly, in the automotive sector, the role of turbulence in drag reduction, vehicle stability, heat dissipation, and aerodynamic shaping is analyzed. Advancements in computational fluid dynamics (CFD), including Reynolds-Averaged Navier-Stokes (RANS), Large Eddy Simulation (LES), and Direct Numerical Simulation (DNS), have enabled researchers to gain deeper insights into turbulence behavior. Experimental techniques such as wind tunnel testing, laser Doppler anemometry (LDA), and particle image velocimetry (PIV) have also been instrumental in validating computational models and refining turbulence control strategies. Various passive and active turbulence control techniques, such as surface modifications, vortex generators, active flow control mechanisms, and adaptive aerodynamics, are discussed in the context of enhancing vehicle efficiency and reducing drag forces. Despite significant advancements, challenges remain in accurately predicting and controlling turbulent shear flows due to their highly nonlinear and multi-scale nature. Future research directions emphasize machine learning-driven turbulence modeling, real-time adaptive control strategies, sustainable aerodynamic designs, and advancements in low-drag, high-efficiency transportation technologies. This review serves as a comprehensive resource for engineers and researchers working toward optimizing turbulent flow effects in aerospace and automotive engineering, ultimately contributing to safer, more efficient, and environmentally sustainable transportation systems.